Metabolic syndrome: An occupational perspective - Nair Chitra (Wolters Kluwer Medknow Publications, 2010)
Objective: To study the prevalence of Metabolic Syndrome (MS) in an Indian industrial setup and to study disparity in occurrence of MS in a working population based on occupational status. Materials and Methods: Cross-sectional study of 651 employees who underwent periodic medical examination. The International Diabetes Federation (IDF) definition of MS and International Standard Classification of Occupations (ISCO)-88 classification of occupations were used. Results: The overall crude prevalence of MS was found to be 18.5%. Nineteen percent of the non-manual workers and 18.3% of the manual workers suffered from MS. The single largest occupational category with MS was ISCO-88 group 1, which included the managers and senior officials. However, no difference was found among the manual and non-manual workers in prevalence of MS.